IJCM_51A: Comorbidities among COPD patients admitted to a tertiary care hospital in Mangalore - Unnikrishnan Bhaskaran; Rathi Priya; Acharya Vishak; Jakhar Fiza; Kowsik Guru Sai; Potti; Khattar Nicita; Mittal Tanvi; Hironi Vidushi; Rekha T; Mithra Prasanna; Kumar Nithin; et al. (Wolters Kluwer Medknow Publications, 2024)
Background: According to WHO, Chronic obstructive pulmonary disease (COPD) associated mortality in India is more than 64.7 estimated age- standardized death rate per 100,000 amongst both sexes. Various studies conducted on COPD, worldwide suggest that patients are more likely to die of comorbid conditions than from COPD. Objective: To find out the various co-morbidities among COPD patientsattending tertiary care hospitals in Mangalore. Methodology: This is a records-based study set in KMC Hospital Attavar, Mangalore. Records of all the COPD patients who attended the hospital in the last 2 years (2016-2017) in KMC Attavar were collected. Case files in which more than 50% of data is incomplete were excluded. Results: A total of 473 COPD patients were admitted in the last two years in KMC Attavar Hospital. The Mean (SD) age of patients was 68 (10) years. Males were found to be affected in a larger proportion than females. Median (IQR) duration of diseases was 2.28(1, 2) years. The maximum duration was 22 years and the minimum was 2 months. GOLD's classification was available for 66 patients, wherein most of the patients had moderate to severe forms of COPD. Around 408(86%) of the COPD patients had one or the other comorbidities. Most COPD patients suffered from metabolic disorders (58%) common being HTN (66%) and DM (45%). The mortality rate was 5.7% which corresponds to 27 patients, with the most common cause being respiratory failure followed by sepsis. Conclusion: The most common comorbidity among COPD patients was Diabetes mellitus and Hypertension so the patients should also be screened for the same in the hospital. The most common cause of mortality seen among COPD patients was Respiratory failure which is a complication of COPD so it should also be kept in mind during treatment.